Lightweight single-component fireproof sealing filler and preparation method thereof

By using materials such as alumina fibers and magnesium hydroxide composites in the sealing filler, combining Zr-MOF and organophosphorus compounds, a lightweight single-component fire-resistant sealing filler is solved, and the sealing filler in the prior art is large in weight and poor thermal conductivity. , the complex construction problem achieves efficient sealing and fire resistance.

CN119161856APending Publication Date: 2024-12-20SHANGHAI SI HI TECH MATERIALS TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411234457.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing sealing filler cannot meet the requirements of light weight, low thermal conductivity, good flame retardant performance and simplified construction during the construction of ship cables, resulting in high construction difficulty and high cost.

Method used

Using flame retardant filler with alumina fibers and magnesium hydroxide composite as matrix, the surface is grown with amino groups, and the organic phosphorus compound is modified, combining calcium hemihydrate sulfate, aluminosilicate, polyvinyl alcohol, Cellulose ether, gypsum retarder, defoaming agent and sodium acetate trihydrate form a lightweight one-component fire-resistant sealing filler.

Benefits of technology

It achieves the effects of good sealing, excellent fire resistance, good mechanical properties and easy to use, reduces the thermal conductivity and construction costs of sealing fillers, and improves working efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005027307440000091
    Figure BDA0005027307440000091
  • Figure BDA0005027307440000101
    Figure BDA0005027307440000101
  • Figure BDA0005027307440000111
    Figure BDA0005027307440000111
Patent Text Reader

Abstract

The invention provides a lightweight single-component fireproof sealing filler. The lightweight single-component fireproof sealing filler comprises calcium sulfate hemihydrate, aluminosilicate, polyvinyl alcohol, cellulose ether, titanium dioxide, a gypsum retarder, a defoaming agent, sodium acetate trihydrate and a flame-retardant filler, the flame-retardant filler is prepared by taking a compound of alumina fiber and magnesium hydroxide as a matrix, growing a Zr-MOF material with amino on the surface of the matrix, and finally modifying an organic phosphorus compound. The prepared sealing filler is excellent in fireproof performance, good in flame retardance, light in weight, good in mechanical property and convenient to use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fireproof materials, and in particular to a lightweight single-component fireproof sealing filler and a preparation method thereof. Background Art

[0002] In order to ensure the normal operation of offshore ships or operating platforms, it is necessary to lay cables / pipelines on ships or platforms. When laying cables / pipelines on ships or platforms, cable trenches or openings are often laid to penetrate the bulkheads and decks of ships. However, this operation will destroy the integrity, sealing and fire resistance of the hull structure. In order to ensure the safety of ships or platforms, these places need to be sealed. Sealing fillers are often used for sealing. The selection of sealing fillers requires not only excellent fire resistance, but also good sealing performance, excellent anti-corrosion performance, and convenient on-site construction. In addition, ship design and manufacturing units regard ship weight reduction as a very important part of energy conservation and emission reduction in the ship industry. The weight reduction of ship outfitting products plays a very important role in reducing the overall weight of ships, increasing ship payload, reducing ship energy consumption, and improving the economic benefits of shipping companies. It has become an important topic in energy conservation and emission reduction in the shipbuilding industry. Therefore, sealing fillers also need to have the advantage of light weight.

[0003] Patent application number 200710038800.2 discloses a fireproof sealing filler for ship cable penetration channels and openings and a preparation method thereof. The raw material components and their weight percentages are as follows: 10-20% kaolin, 5-10% talcum powder, and 30-50% silicon powder as base materials; 10-20% aluminum hydroxide, 5-10% hydrated zinc borate, and 10-20% magnesium hydroxide as flame retardants; wherein the ratio of the base material to the flame retardant is 1:1-2.3:1; in addition, coagulants calcium sulfate, calcium chloride, magnesium chloride, and sodium carbonate are added, and the added amount is calculated based on 100% of the total amount of the base material and the flame retardant, and the above four coagulants are added in 20-4% each. First, add water to the coagulant and stir and mix to form a slurry. When actually used, add the slurry to the powdered batch of the base material and the flame retardant, stir with a high-efficiency mixer, and obtain a paste-like fireproof sealing filler after sufficient stirring and mixing. Although the above-mentioned sealing filler has certain flame retardant and sealing effects, it is inconvenient to use as a two-component sealing filler. Moreover, the sealing fillers currently available on the market often cannot meet the significant advantages of the sealing filler, such as light weight, low thermal conductivity, good flame retardant performance, and simple construction. Therefore, how to reduce the weight of the sealing filler, improve the thermal conductivity, flame retardant performance and construction performance of the sealing filler, has very significant economic significance for reducing the weight of the ship and the difficulty of cable / pipeline fire-resistant sealing construction, saving construction costs, and improving work efficiency. Summary of the invention

[0004] The technical problem to be solved by the present invention is: in view of the shortcomings of the prior art, a lightweight single-component fireproof sealing filler and a preparation method thereof are provided. The sealing filler prepared by the present invention not only has excellent fireproof performance, but also has good flame retardancy, light weight, good mechanical properties, and is easy to use.

[0005] In order to solve the above technical problems, the technical solution of the present invention is:

[0006] A lightweight single-component fireproof sealing filler comprises calcium sulfate hemihydrate, aluminum silicate, polyvinyl alcohol, cellulose ether, titanium dioxide, gypsum retarder, defoamer, sodium acetate trihydrate, and flame retardant filler; the flame retardant filler uses a composite of aluminum oxide fiber and magnesium hydroxide as a matrix, a Zr-MOF material with amino groups is grown on the surface of the matrix, and finally an organic phosphorus compound is modified.

[0007] Preferably, the amounts of the components, measured in mass percentage, are 83.0-89.0% calcium sulfate hemihydrate, 8.5-10.0% aluminosilicate, 0.1-0.5% polyvinyl alcohol, 0.1-0.3% cellulose ether, 0.05-0.15% titanium dioxide, 0.05-0.35% gypsum retarder, 0.03-0.15% defoamer, 0.02-0.1% sodium acetate trihydrate, and 2-8% flame retardant filler.

[0008] Preferably, the mass percentage of the aluminosilicate is 8.7-10%, and the mass percentage of the gypsum retarder is 0.07-0.35%.

[0009] Preferably, the aluminosilicate is kaolin, and / or the organophosphorus compound is diphenylphosphine.

[0010] Preferably, the method for preparing the flame retardant filler comprises the following steps:

[0011] S1: mixing a mixed dispersion of magnesium hydroxide and aluminum oxide with a metal salt and an organic ligand to obtain a reaction solution;

[0012] S2: heating the reaction solution to react;

[0013] S3: After the reaction is completed, the reaction solution is filtered, and the filtered precipitate is washed and dried to obtain a modified magnesium hydroxide / alumina fiber composite;

[0014] S4: Mix the modified magnesium hydroxide / aluminum oxide fiber composite, paraformaldehyde and alcohol solvent, add diphenylphosphine solution, heat and react, filter the reaction solution after the reaction, wash the precipitate and dry it to obtain a flame retardant filler.

[0015] Preferably, in step S1, the metal salt is one of zirconium nitrate and zirconium chloride, the organic ligand is 2-aminoterephthalic acid, and the molar ratio of the metal salt to the organic ligand is 1:1; and / or the mass ratio of the magnesium hydroxide, aluminum oxide and the metal salt is (1-2): (1-2): 1.

[0016] Preferably, in step S2, the temperature of the temperature-raising reaction is 115-125° C., and the time is 12-24 hours.

[0017] Preferably, in step S3, the drying temperature is 70-80° C., and the drying time is 24-48 hours.

[0018] Preferably, in step S4, the alcohol solvent is methanol, and the usage ratio of the modified magnesium hydroxide / aluminum oxide fiber composite, paraformaldehyde, alcohol solvent, and diphenylphosphine is 2g:0.5g:50ml:(1-2)g.

[0019] Preferably, in step S4, the temperature of the temperature-raising reaction is 55-65° C., and the time is 5-6 h; nitrogen is introduced during the reaction for protection.

[0020] In order to better solve the above technical problems, the present invention also discloses a method for preparing a lightweight single-component fireproof sealing filler:

[0021] A: Weigh each raw material according to the measurement ratio;

[0022] B: Add the weighed raw materials into a blender and mix them evenly to obtain the product.

[0023] The lightweight single-component fireproof sealing filler provided by the present invention can be used after adding water, mixing and stirring.

[0024] Due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0025] The present invention provides a lightweight single-component fireproof sealing filler, comprising calcium sulfate hemihydrate, aluminum silicate, polyvinyl alcohol, cellulose ether, titanium dioxide, gypsum retarder, defoamer, sodium acetate trihydrate, and flame retardant filler; the sealing filler has not only good sealing performance and excellent fireproof performance, but also has the advantages of light weight, good mechanical properties, etc., and is easy to use.

[0026] The flame retardant filler provided by the present invention is a composite of alumina fiber and magnesium hydroxide as a matrix, a Zr-MOF material with amino groups is grown on its surface, and finally an organic phosphorus compound is modified. Magnesium hydroxide can effectively reduce the flammability of the material as a flame retardant, and the amino-modified Zr-MOF can further enhance its flame retardant effect, forming a multiple flame retardant mechanism. The addition of alumina fiber improves the strength and rigidity of the material, making the sealing filler more stable under mechanical stress. Finally, the modification of the organic phosphorus compound further improves the flame retardant properties of the material. DETAILED DESCRIPTION

[0027] In order to more clearly understand the above-mentioned objectives, features and advantages of the present invention, the scheme of the present invention will be further described below. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

[0028] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present invention, rather than all of the embodiments.

[0029] In order to solve the problem that the fireproof sealing filler in the prior art cannot meet the requirements of light weight, low thermal conductivity, good flame retardancy, and simple construction, the present invention provides a new fireproof sealing filler.

[0030] A lightweight single-component fireproof sealing filler comprises calcium sulfate hemihydrate, aluminum silicate, polyvinyl alcohol, cellulose ether, titanium dioxide, gypsum retarder, defoamer, sodium acetate trihydrate, and flame retardant filler; the flame retardant filler uses a composite of aluminum oxide fiber and magnesium hydroxide as a matrix, a Zr-MOF material with amino groups is grown on the surface of the matrix, and finally an organic phosphorus compound is modified.

[0031] In fireproof sealing fillers, calcium sulfate hemihydrate is the main base material, which has certain fireproof properties and can provide structural support; the addition of an appropriate amount of aluminum silicate and compounding it with calcium sulfate hemihydrate as a base material can not only provide the material with heat resistance and fire resistance, but also improve the mechanical strength of the material; the addition of polyvinyl alcohol effectively improves the adhesion of the components in the material, and its compounding with cellulose ether improves the fluidity and processing performance of the material; titanium dioxide is added as a color filler to effectively improve the weather resistance and mechanical properties of the fireproof sealing filler; gypsum retarder can effectively adjust the solidification time of the material to ensure the operable time of the fireproof sealing filler during the construction process; defoaming agent can eliminate bubbles generated during the construction process to ensure good sealing performance; sodium acetate trihydrate is used to adjust the viscosity and rheological properties of the material; the addition of flame retardant fillers effectively improves the fireproof performance and thermal conductivity of the sealing filler while ensuring good sealing performance of the filler.

[0032] In some embodiments, the flame retardant filler uses a composite of alumina fiber and magnesium hydroxide as a matrix to increase the fire resistance of the material and reduce the flame propagation speed; Zr-MOF material with amino groups is grown on the surface of the composite of alumina fiber and magnesium hydroxide, and an organic phosphorus compound is modified to form a three-in-one flame retardant filler, which combines the three flame retardant functions of Mg(OH), Zr-MOF and phosphorus.

[0033] In some embodiments, the amount of each component is calculated by mass percentage, respectively, calcium sulfate hemihydrate 83.0-89.0%, aluminum silicate 8.5-10.0%, polyvinyl alcohol 0.1-0.5%, cellulose ether 0.1-0.3%, titanium dioxide 0.05-0.15%, gypsum retarder 0.05-0.35%, defoamer 0.03-0.15%, sodium acetate trihydrate 0.02-0.1%, flame retardant filler 2-8%. The present invention optimizes the amount of the above components to obtain a sealing filler that not only has good sealing performance, but also has the advantages of low thermal conductivity, high flame retardancy, etc.

[0034] In some embodiments, the mass percentage of the aluminosilicate may be preferably 8.7-10%, and the mass percentage of the gypsum retarder may be preferably 0.07-0.35%.

[0035] In some embodiments, the aluminosilicate is kaolin. Kaolin not only has good fire resistance, but also good chemical stability. Kaolin also has low shrinkage, and has good filling properties during drying and curing, and can maintain good sealing properties to avoid cracks.

[0036] In some embodiments, the method for preparing the flame retardant filler comprises the following steps:

[0037] S1: mixing a mixed dispersion of magnesium hydroxide and aluminum oxide with a metal salt and an organic ligand to obtain a reaction solution;

[0038] S2: heating the reaction solution to react;

[0039] S3: After the reaction is completed, the reaction solution is filtered, and the filtered precipitate is washed and dried to obtain a modified magnesium hydroxide / alumina fiber composite;

[0040] S4: Mix the modified magnesium hydroxide / aluminum oxide fiber composite, paraformaldehyde and alcohol solvent, add diphenylphosphine solution, heat and react, filter the reaction solution after the reaction, wash the precipitate and dry it to obtain a flame retardant filler.

[0041] Magnesium hydroxide, alumina fiber, Zr-MOF and phosphorus compounds all have good flame retardant properties. The present invention adopts a solvent thermal method and a chemical grafting method. First, a Zr-MOF material with an amino group is grown on the surface of a composite of magnesium hydroxide and alumina fiber, and then an organic phosphine compound is grafted. The obtained flame retardant filler not only has good flame retardant properties, but also can well reduce the thermal conductivity of the sealing filler and improve the fire resistance of the sealing filler. In addition, the flame retardant filler has good mechanical properties and can also improve the flexural strength and compressive strength of the fireproof sealing filler to a certain extent.

[0042] In some embodiments, in step S1, the metal salt is one of zirconium nitrate and zirconium chloride, the organic ligand is 2-aminoterephthalic acid, and the molar ratio of the metal salt to the organic ligand is 1:1; and / or the mass ratio of the magnesium hydroxide, aluminum oxide, and the metal salt is (1-2): (1-2): 1.

[0043] In some embodiments, in step S2, the temperature of the temperature-raising reaction is 115-125° C., and the time is 12-24 hours.

[0044] In some embodiments, in step S3, the drying temperature is 70-80° C., and the drying time is 24-48 hours.

[0045] In some embodiments, in step S4, the alcohol solvent is methanol, and the usage ratio of the modified magnesium hydroxide / aluminum oxide fiber composite, paraformaldehyde, alcohol solvent, and diphenylphosphine is 2g:0.5g:50ml:(1-2)g.

[0046] In some embodiments, in step S4, the temperature of the temperature-raising reaction is 55-65° C., and the time is 5-6 hours; nitrogen is introduced during the reaction for protection.

[0047] The present invention selects an organic ligand with an amino group to react, so that the amino group on the surface of Zr-MOF reacts with -PH in the organic phosphine compound, thereby being grafted onto the composite surface of magnesium hydroxide and aluminum oxide fiber.

[0048] In order to better solve the above technical problems, the present invention also discloses a method for preparing a lightweight single-component fireproof sealing filler:

[0049] A: Weigh each raw material according to the measurement ratio;

[0050] B: Add the weighed raw materials into a blender and mix them evenly to obtain the product.

[0051] The lightweight single-component fireproof sealing filler provided by the present invention can be used after adding water and mixing. When adding water and mixing, the mass ratio of the filler to water is controlled to be 2:1.

[0052] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.

[0053] The performance parameters of the raw materials in the following examples and comparative examples are as follows:

[0054] Kaolin: fineness is 3000 mesh;

[0055] Polyvinyl alcohol: PVA1788;

[0056] Cellulose ether: Hydroxypropyl methylcellulose, with a viscosity of 45000mPa·s;

[0057] Alumina fiber: α-alumina, length: 50 mm, diameter: 3 μm;

[0058] Titanium dioxide: rutile type, average particle size is 10±1μm.

[0059] Unless otherwise specified, other raw materials are commercially available.

[0060] Example 1

[0061] A method for preparing a lightweight single-component fireproof sealing filler comprises the following steps:

[0062] (1) 1 g of magnesium hydroxide and 1 g of alumina fiber were added to 80 ml of DMF and mixed evenly to obtain a dispersion. 1 g of zirconium nitrate and 2-aminoterephthalic acid (the molar ratio of 2-aminoterephthalic acid to zirconium nitrate was controlled to be 1:1) were added to the dispersion. After stirring and mixing evenly, the reaction solution was transferred to a hydrothermal autoclave and reacted at 120° C. for 20 h. After the reaction was completed, the mixture was cooled to room temperature, the reaction solution was filtered, the precipitate was washed, and then dried at 70° C. for 48 h to obtain a modified magnesium hydroxide / alumina fiber composite.

[0063] (2) Under nitrogen protection, 2 g of the modified magnesium hydroxide / aluminum oxide fiber composite, 0.5 g of paraformaldehyde, and 50 ml of methanol were mixed, and a diphenylphosphine solution (prepared by mixing 2 g of diphenylphosphine and 20 ml of methanol) was added, and the temperature was raised to 60° C. for reaction for 6 h. After the reaction was completed, the reaction solution was filtered, the precipitate was washed, and then dried to obtain a flame retardant filler;

[0064] (3) According to the metering ratio, weigh 85 g of calcium sulfate hemihydrate, 9 g of kaolin, 0.2 g of polyvinyl alcohol, 0.1 g of hydroxypropyl methylcellulose, 0.1 g of titanium dioxide, 0.1 g of gypsum retarder, 0.1 g of silicone defoamer, 0.1 g of sodium acetate trihydrate, and 5.3 g of flame retardant filler;

[0065] (4) Add the above raw materials into a mixer, stir and mix them evenly to obtain a fireproof sealing filler.

[0066] Example 2

[0067] Compared with Example 1, the formula of the fireproof sealing filler is 84g of calcium sulfate hemihydrate, 9g of kaolin, 0.2g of polyvinyl alcohol, 0.1g of hydroxypropyl methylcellulose, 0.1g of titanium dioxide, 0.1g of gypsum retarder, 0.1g of silicone defoamer, 0.1g of sodium acetate trihydrate, and 6.3g of flame retardant filler, and other conditions are the same as those in Example 1.

[0068] Example 3

[0069] Compared with Example 1, the formula of the fireproof sealing filler is 83.5g of calcium sulfate hemihydrate, 9g of kaolin, 0.2g of polyvinyl alcohol, 0.1g of hydroxypropyl methylcellulose, 0.1g of titanium dioxide, 0.1g of gypsum retarder, 0.1g of silicone defoamer, 0.1g of sodium acetate trihydrate, and 6.8g of flame retardant filler, and other conditions are the same as those in Example 1.

[0070] Example 4

[0071] Compared with Example 1, the formula of the fireproof sealing filler is 84g of calcium sulfate hemihydrate, 10.0g of kaolin, 0.2g of polyvinyl alcohol, 0.1g of hydroxypropyl methylcellulose, 0.1g of titanium dioxide, 0.1g of gypsum retarder, 0.1g of silicone defoamer, 0.1g of sodium acetate trihydrate, and 5.3g of flame retardant filler, and other conditions are the same as those in Example 1.

[0072] Comparative Example 1

[0073] Compared with Example 1, when preparing the flame retardant filler, an equal amount of magnesium hydroxide was used to replace the aluminum oxide fiber, and other conditions were the same as in Example 1.

[0074] Comparative Example 2

[0075] Compared with Example 1, when preparing the flame retardant filler, an equal amount of alumina fiber is used to replace magnesium hydroxide, and other conditions are the same as in Example 1.

[0076] Comparative Example 3

[0077] Compared with Example 1, when preparing the flame retardant filler, magnesium hydroxide and alumina fiber are not added, and other conditions are the same as those in Example 1.

[0078] Comparative Example 4

[0079] Compared with Example 1, step (2) is not included, and other conditions are the same as those in Example 1.

[0080] Comparative Example 5

[0081] Compared with Example 1, no flame retardant filler is added to the fireproof sealing filler, and other conditions are the same as those in Example 1.

[0082] The fireproof sealing fillers prepared in the above embodiments and comparative examples were subjected to performance tests, and the test results are shown in Table 1, wherein the fire resistance rating was tested in accordance with Part 3 of the IMO 2010FTP Rules; Articles 3 and 9 of Chapter II-2 of the 1974 International Convention for the Safety of Life at Sea and its amendments.

[0083] Table 1

[0084]

[0085]

[0086]

[0087] It can be seen from the test results in Table 1 that the fireproof sealing filler prepared by the present invention not only has the advantages of light weight and good mechanical properties, but also has good sealing performance, excellent fireproof performance, low thermal conductivity, and is asbestos-free, halogen-free, acid-resistant, alkali-resistant, oil-resistant, and seawater-resistant.

[0088] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.

Claims

1. A lightweight single-component fireproof sealing filler, characterized in that: The invention comprises calcium sulfate hemihydrate, aluminum silicate, polyvinyl alcohol, cellulose ether, titanium dioxide, gypsum retarder, defoamer, sodium acetate trihydrate and flame retardant filler; the flame retardant filler takes a composite of aluminum oxide fiber and magnesium hydroxide as a matrix, grows a Zr-MOF material with amino groups on the surface of the matrix, and finally modifies the organic phosphorus compound.

2. A lightweight single-component fireproof sealing filler according to claim 1, characterized in that: The dosage of each component is calculated by mass percentage, which is 83.0-89.0% of calcium sulfate hemihydrate, 8.5-10.0% of aluminosilicate, 0.1-0.5% of polyvinyl alcohol, 0.1-0.3% of cellulose ether, 0.05-0.15% of titanium dioxide, 0.05-0.35% of gypsum retarder, 0.03-0.15% of defoamer, 0.02-0.1% of sodium acetate trihydrate and 2-8% of flame retardant filler.

3. The lightweight single-component fireproof sealing filler according to claim 1, characterized in that: The mass percentage of the aluminosilicate is 8.7-10%, and the mass percentage of the gypsum retarder is 0.07-0.35%.

4. The lightweight single-component fireproof sealing filler according to claim 1, characterized in that: The aluminosilicate is kaolin, and / or the organic phosphorus compound is diphenylphosphine.

5. A lightweight single-component fireproof sealing filler according to claim 4, characterized in that: The preparation method of the flame retardant filler comprises the following steps: S1: mixing a mixed dispersion of magnesium hydroxide and aluminum oxide with a metal salt and an organic ligand to obtain a reaction solution; S2: heating the reaction solution to react; S3: After the reaction is completed, the reaction solution is filtered, and the filtered precipitate is washed and dried to obtain a modified magnesium hydroxide / alumina fiber composite; S4: Mix the modified magnesium hydroxide / aluminum oxide fiber composite, paraformaldehyde and alcohol solvent, add diphenylphosphine solution, heat and react, filter the reaction solution after the reaction, wash the precipitate and dry it to obtain a flame retardant filler.

6. A lightweight single-component fireproof sealing filler according to claim 5, characterized in that: In step S1, the metal salt is one of zirconium nitrate and zirconium chloride, the organic ligand is 2-aminoterephthalic acid, the molar ratio of the metal salt to the organic ligand is 1:1; and / or the mass ratio of the magnesium hydroxide, aluminum oxide and the metal salt is (1-2): (1-2):

1.

7. The lightweight single-component fireproof sealing filler according to claim 5, characterized in that: In step S2, the temperature of the temperature-raising reaction is 115-125° C., and the time is 12-24 hours.

8. The lightweight single-component fireproof sealing filler according to claim 5, characterized in that: In step S4, the alcohol solvent is methanol, and the usage ratio of the modified magnesium hydroxide / aluminum oxide fiber composite, paraformaldehyde, alcohol solvent, and diphenylphosphine is 2g:0.5g:50ml:(1-2)g.

9. The lightweight single-component fireproof sealing filler according to claim 5, characterized in that: In step S4, the temperature of the temperature-raising reaction is 55-65° C., and the time is 5-6 hours; nitrogen is introduced during the reaction for protection.

10. A method for preparing a lightweight single-component fireproof sealing filler according to any one of claims 1 to 9, characterized in that: The following steps are involved: A: Weigh each raw material according to the measurement ratio; B: Add the weighed raw materials into a blender and mix them evenly to obtain the product.

Citation Information

Cited By

  • Flame-retardant alumina fiber-containing cable outer sheath material

    CN120383768A